Analysis of Flood Vulnerability Assessment in Urban Area (Case Study: North Semarang District) - Undayani Cita Sari; Raden Harya Dananjaya (Universitas Islam Sultan Agung, 2020)
The disasters occurred in Semarang, as the capital city of Central Java, must be considered. This is because it can cause various impacts that can affect the wheels of government. One of the problems which continously occur in the Semarang city is flood. Flood can cause a variety of damage and losses both of material and non-material. This flood can be caused by various factors. In this study, analysed the causes of flooding that occurred in the Semarang City. The location in this study specifically was in the North Semarang District. Analysis was done using scoring analysis with approach method based on preview research. The scoring method performed by Haryani et al. (2012) was adopted in this study. This method used five variables. The variables were rainfall, land coverage, slope shape, land system, and elevation. According to analysis, it shows that four of five variables which are land coverage, slope shape, land system, and elevation, which related to topography and land use, have maximum score to influence the occurrence of flooding in North Semarang District. Accordingly, the North Semarang Subdistrict is categorized as prone to flood hazard. Moreover, with a lot of human activities as result of increasing the population growth, it influences the land use of North Semarang District which further increases the vulnerability of North Semarang District to flooding.